Institutional Human Resources Challenges and Quality Assurance in Universities in The Gambia - Mbowe, Isatou; Sawaneh, Banna; Badjie, Gibriel (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: This study aims to evaluate the Institutional Human Resources Challenges and Quality Assurance in Universities in The Gambia. Design/Methode/Approach: The study adopts a descriptive survey design, utilizing a mixed method approach involving the use of questionnaires (self-administered, online surveys, Google Forms) and conducting interviews. The sampling technique employed is proportional to size with a sample size of 248. Research Finding: The research findings reveal that there is adequate human resource capacity for quality assurance in universities in The Gambia. However, the findings also indicate inadequate financial resources in these universities to support quality assurance procedures. Furthermore, the research findings provide insights into how problems with institutional human resources affect the university systems selected to ensure the quality of higher education. Additionally, the study uncovers challenges in managing human resources at universities, including managing employee relations, retaining qualified workers, providing strong leadership support, fostering a positive work environment, promoting diversity and inclusion, and empowering university leaders. Theoretical contribution/Originality: The theoretical contribution of this study is to strengthen understanding of how human resource issues impact university capacity in ensuring effective quality assurance. Practitioner/Policy implication: The practical and policy implications of this study underscore the need for greater attention to human resource issues in Gambian universities to enhance the effectiveness of quality assurance processes. Research limitation: Limitations of this study include sample size constraints, limitations in the methodology employed, and geographic constraints in research coverage.